1996
DOI: 10.1136/bmj.312.7046.1576
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of smoking in Delhi: cross sectional study

Abstract: Objective-To determine the prevalence and predictors of smoking in urban India.Design-Cross sectional. Setting-Delhi, urban India, 1985-6. Subjects-Random sample of 13 558 men and women aged 25-64 years.Main outcome measure-Smoking prevalence; subjects who were currently smoking and who had smoked > 100 cigarettes or beedis or chuttas in their lifetime were defined as smokers.Results-45% (95% confidence interval 43.8 to 46.2) of men and 7% (6.4 to 7.6) of women were smokers. Education was the strongest predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
3
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 14 publications
7
40
3
1
Order By: Relevance
“…[3] Education entered into the model first as the strongest predictor of smoking (P < 0.001) among both men and women. [5] Smoking prevalence was high in illiterates and in literates with less than seven years of schooling, but decreased significantly with the increase in education status after attaining secondary education and more. [6] Men with no education were 1.8 times more likely to be smokers than men with college education, and women with no education were 3.7 times more likely than those with college education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Education entered into the model first as the strongest predictor of smoking (P < 0.001) among both men and women. [5] Smoking prevalence was high in illiterates and in literates with less than seven years of schooling, but decreased significantly with the increase in education status after attaining secondary education and more. [6] Men with no education were 1.8 times more likely to be smokers than men with college education, and women with no education were 3.7 times more likely than those with college education.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Men with no education were 1.8 times more likely to be smokers than men with college education, and women with no education were 3.7 times more likely than those with college education. [5] Occupation is one category highly relevant to social disparities in health. People in manual occupations were more likely to smoke than those in professional or supervisory occupations.…”
Section: Introductionmentioning
confidence: 99%
“…20 In Naryan et al study, men with no education were 1.8 times more likely to be smokers than men with college education. 21 In Prabakar et al study also, prevalence of smoking decreased as educational status became higher. 19 Majority of males (44.2%) were skilled workers.…”
Section: Discussionmentioning
confidence: 83%
“…The study by Venkat Narayan et al, done in Delhi also found a similar association between higher income categories and cigarette smoking. [10] With respect to policy for tobacco control, the fi ndings of this section suggest that in order to control tobacco use among this section of the population efforts shall have to be directed for control of both the smokeless (especially among the younger age groups) tobacco use and smoking. With respect to smoking, the efforts shall have to be concentrated on ways and means to curb beedi smoking.…”
Section: Factors Impacting On Form Of Tobacco Consumedmentioning
confidence: 99%
“…[9,10] Hence, the impact of other factors on the type of tobacco consumed was examined both independently and after controlling for literacy level.…”
Section: Factors Impacting On Form Of Tobacco Consumedmentioning
confidence: 99%